Treatment of pain in oncological patients - Yoselyn Lázara Díaz Juvier; Yannarys Hernández Ortega; Lázaro Abilio Hernández Rodríguez; Olga Lidia Cuevas Pérez; Diana Rosa Fernández Ruiz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Uncontrolled oncological pain is one of the symptoms that negatively affect the physical and psychological health of patients diagnosed with cancer. Undoubtedly, it represents a particularly dramatic situation. There is evidence about pain control benefits of in these patients; to achieve them, it is necessary to assess the causes, location, intensity and duration of pain before and during treatment. Different ways of measuring pain intensity are proposed, and the analog visual scale is one of the most common, in addition to being the most used internationally with respect to the rest of the single-dimensional scales. The World Health Organization proposes the use of the analgesic ladder in a prescribed manner, with the corresponding titration of the analgesic need, as well as the necessary coadjutant treatments. Standardizing treatments correctly and evaluating their response, is essential for pain control. The present bibliographic review proposes an overlook to the international guidelines in the therapeutic approach of this condition, and with it, it offers an update on the topic.